Teleworking and Life Satisfaction during COVID-19: The Importance of Family Structure - Claudia Senik; Andrew E. Clark; Conchita D'Ambrosio; Anthony Lepinteur; Carsten Schröder (Institute of Labor Economics (IZA), 2022)
We carry out a difference-in-differences analysis of a representative real-time survey conducted as part of the German Socio-Economic Panel (SOEP) study and show that teleworking had a negative average effect on life satisfaction over the first two years of the COVID-19 pandemic. This average effect hides considerable heterogeneity reflecting genderrole asymmetry: lower life satisfaction is only found for unmarried men and women with school-age children. The negative effect for women with school-age children disappears in 2021, suggesting adaptation to new constraints and/or the adoption of coping strategies.
Keywords: I31; M5; 330; life satisfaction; teleworking; work from home; gender; childcare; COVID-19; SOEP